Assessment of bank financial performance and its impact on profit of national private banks - Chairul Anam (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2017)
The purpose of this study is to determine the effect of financial performance of banks ; Non Performing Loan (NPL), Loan To Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), and Net Interest Margin (NIM) on Return On Assets (ROA). This study was conducted using secondary data. The sampling technique uses purposive sampling with 7 companies. The method used is multiple linear regression. The result of analysis shows that partially Non Performing Loan (NPL) has significant effect to ROA, while Loan To Deposit Ratio (LDR), Capital Adequacy Ratio (CAR) and Net Interest Margin (NIM) have no significant effect on ROA. Simultaneously that Non Performing Loan (NPL), Loan To Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), and Net Interest Margin (NIM) have significant effect to ROA.